1992
DOI: 10.1021/jf00015a011
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of glycoalkaloids in potato plants and commercial potato products

Abstract: As part of a program to control the biosynthesis of Solanum glycoalkaloids in potatoes, we used a modified extraction-HPLC assay to measure the -chaconine and -solanine content of commercial and new potato varieties, different parts of the potato plant, and commercial potato products. The improved assay was accomplished by extracting, precipitating, and filtering the hot methanol extract through a 0.45-µ membrane before HPLC analysis. Recoveries of spiked samples ranged from 89 to 95%. The combined -chaconine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
115
0
9

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(139 citation statements)
references
References 30 publications
15
115
0
9
Order By: Relevance
“…Glycoalkaloids content (Table 1) generally was quite stable after cooking, in accordance with previous data reported on potato (Friedman & Si Dao, 1992). This is demonstrated by the general trend of total glycoalkaloids (Table 1) that showed an increase after grilling and a decrease after boiling, caused, as previously stated, by a water loss (concentration) and by a leaching (dilution), respectively.…”
Section: Chemical Compositionsupporting
confidence: 90%
“…Glycoalkaloids content (Table 1) generally was quite stable after cooking, in accordance with previous data reported on potato (Friedman & Si Dao, 1992). This is demonstrated by the general trend of total glycoalkaloids (Table 1) that showed an increase after grilling and a decrease after boiling, caused, as previously stated, by a water loss (concentration) and by a leaching (dilution), respectively.…”
Section: Chemical Compositionsupporting
confidence: 90%
“…nema et al [23] reported that Tga content in frozen peels of different edible varieties ranged from 6.5 to 12.1 mg 100 g −1 f.w. Many authors, Friedman and Dao [6], Wünsch and Munzert [39], Friedman [5], and Friedman and levin [7], reported that most Tga in the tuber are accumulated in the peel, especially in the area of eyes, whereas the distribution of Tga in a tuber differs among varieties. Some researchers, Wünsch and Munzert [39], Friedman and McDonald [8], Pęksa et al [26], Friedman [8], Tajner-Czopek et al [37] and Ostry et al [25], think that there may occur significant differences in Tga content among of the same varieties.…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of α-solanine to α-chaconine varies between varieties, although α-chaconine usually occurs in distinctly higher concentration than α-solanine [6,8,16,23,30,37]. The scientific literature most frequently has provided data on the ratio of α-solanine to α-chaconine in lightfleshed varieties.…”
Section: Tga Content After Peelingmentioning
confidence: 99%
“…A number of different columns and elution protocols for many different compounds or compound classes have been developed and successfully applied for metabolic studies. Methods exist for small sugar analysis [15], amino acids [41], nucleotides [57,68], flavonoids [59], volatiles [6], or alkaloids [30].…”
Section: Metabolomics Approachesmentioning
confidence: 99%